Application of bacterial nanocellulose fibers as reinforcement in cement composites. (30th April 2020) - Akhlaghi, Mohammad Amir; Bagherpour, Raheb; Kalhori, Hamid
Highlights: BNC improve mechanical properties of cement mortars. Coating polypropylene fibers with BNC improve fiber-cement interactions. BNC-powder exhibited better behavior compared to BNC-gel. Cellulosic nano-fibers increase homogeneity by filling the pores. Abstract: In this study, the potential effect of bacterial nano-cellulose on mechanical properties of cement mortar was evaluated. For this purpose, bacterial nano-cellulose (BNC) directly as powder and gel (0.1, 0.3, and 0.5 wt%), and indirectly as coated onto the polypropylene fibers were used in the preparation of cement paste in order to investigate the effect of each method on the flexural strength, compressive strength and water absorption of specimens. Results indicated that samples containing BNC gel and powder enhanced mechanical properties. However, BNC-gel indicated inferior properties compared to powder. The maximum increase in flexural strength between all samples was observed in the specimens containing 0.5% of BNC powder, which was 104%, compared to the control sample. In addition, utilizing nanofibers decreased the water absorption of cement mortar. The water absorption of specimens containing 0.1% of the gel fibers and 0.3% of powder was decreased by 26% and 37%, respectively. According to scanning electron microscopy (SEM) analysis, the roughness and specific surface of polypropylene fibers coated with BNC were increased. This can improve the interaction of these fibers with the cement matrix. The results show clearly that the application of BNC nanofibers improves the mechanical properties of cement paste and workability of polypropylene fibers.